Compression properties of gas diffusion layers and its constitutive model under cyclic loading. (26th April 2021) - Meng, Lei; Zhou, Ping; Yan, Ying; Guo, Dongming
Abstract: The compressive deformation of gas diffusion layer (GDL), which is highly nonlinear and related to the loading history, affects the performance of PEM fuel cell stacks. However, linear elastic models are widely used. In this study, a new nonlinear constitutive model is proposed to describe the compression properties. Macroscopic studies reveal that GDL has different mechanical properties during the first and repeated compression stages. Besides, the tangent modulus has a significant linear relationship with stress. The constitutive model can be rebuilt using the micro-mechanical theory of fiber assemblies by considering the bending of carbon fibers. Furthermore, a prediction method is proposed to describe cyclic compression behavior. The prediction results fit well with the test results with an average and maximum relative error of less than 5.30% and 18.13%, respectively. These conclusions are beneficial to the design of GDL with specific mechanical properties and the real-time analysis of PEM fuel cell. Highlights: GDL has different mechanical properties during the first and repeated compression stages. The linear relationship between tangent modulus and stress is revealed. A nonlinear constitutive model is developed. A method is proposed to predict the cyclic compression properties of GDL.